Multiple roles of ALDH1 in health and disease - Zhao, Wenqi; Xia, Yu; Gao, Zhiqi; Chen, Jian; Zhang, Erlong (Frontiers in Physiology, 2025)
Aldehyde dehydrogenase 1 (ALDH1) is an important aldehyde-metabolizing enzyme that plays a key role in various biological processes, such as regulating cellular growth, modulating retinoic acid (RA) signaling pathways, and contributing to stem cell function. It is recognized as a crucial biomarker not only because of its significant involvement in the occurrence and development of various cancers but also because it is an important prognostic indicator for cancer progression. Furthermore, recent research has provided substantial evidence that the multiple roles of ALDH1 extend beyond cancer, with significant progress in understanding its mechanisms in other diseases and its clinical applications. These findings provide potential therapeutic targets for the future treatment of other diseases. In this review, we summarize the current understanding of the biological functions of ALDH1, the molecular mechanisms of its transcription and regulation, and the progress in cancer research related to the ALDH1 family. We not only discuss the mechanisms of ALDH1 in cancer but also its research development and potential pathological mechanisms in other diseases. The role of ALDH1 in various diseases is complex, and its expression levels are highly important for disease diagnosis, treatment, and prognosis. Future in-depth studies on ALDH1 functions are expected to provide new strategies and directions for the treatment of related diseases.